A sleep behaviour intervention to improve cardiometabolic health in adults with overweight and obesity - Henst, Rob HP (Department of Human Biology, 2021)
Rob Henricus Petrus Henst was born on the 12th of March in Schaijk, the Netherlands. He graduated from pre-vocational secondary education (VMBO) in 2005 and continued to study process and laboratory technology at an intermediate vocational educational (MBO) institution. In 2009, Rob started with a Bachelor of Science degree, majoring in Life Science with a minor in Exercise Science. For his undergraduate thesis in 2012, he moved to South Africa where he was introduced to chronobiology in exercise science. In 2013, Rob continued to study in South Africa for his Master of Science (Exercise Science) degree and published his first peer-reviewed article in the Journal of Biological Rhythms. He then developed an interest in sleep and cardiometabolic health, specifically in the context of public health. In 2015, these interests were combined and lead to his current PhD thesis on a sleep behaviour intervention for the betterment of cardiometabolic health. In this year, he also co-founded the business unit Sleep Science within the Sports Science Institute of South Africa to help individuals sleep better. In 2019, Rob moved back to the Netherlands to write the final pages of his PhD thesis.